СONCENTRATION OF ANTI-INFLAMATORY CYTOKINES IN CELL CULTURE SUPERNATANTS IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS - I. M. Krivolapova (SPb RAACI, 2019)
Juvenile idiopathic arthritis is a chronic inflammatory disease of the joints in children, mainly of autoimmune or auto-inflammatory nature. It is a heterogeneous group, which includes different subtypes of the disease. Different mechanisms may play role in the pathogenesis of distinct subtypes of juvenile arthritis. However, a long-term imbalance of pro- and anti-inflammatory cytokines is important for all subtypes of disease. The aim of the present study was to determine spontaneous and stimulated anti-inflammatory cytokines production by peripheral blood cells from the children with juvenile idiopathic arthritis. Patients of 2 to 17 years old with different subtypes of juvenile idiopathic arthritis (n = 99) and healthy children without signs of autoimmune diseases (control, n = 31) were examined. Spontaneous and phytohemagglutinin-stimulated concentrations of IL-1ra, IL-4, IL-10, TGF-β in supernatants of whole-blood cultures were determined by ELISA. Differences in the spontaneous and mitogen-stimulated secretion of the cytokines in patients with different subtypes of juvenile arthritis have not been revealed. The spontaneous IL-1ra, IL-4 and IL-10 production by blood cells in the common group of patients with juvenile idiopathic arthritis was similar to the controls. The median value of spontaneous TGF-β concentration in the patients was below the detection level, whereas blood cells of healthy children had a higher potential of spontaneous TGF-β production. IL-4 and IL-10 production after incubation of peripheral blood cells with phytohemagglutinin in patients and in the control group did not differ from the controls, while IL-1ra and TGF-β synthesis was significantly lower than in healthy children.The spontaneous and/or stimulated production of IL-1ra, TGF-β by blood cells in children with juvenile idiopathic arthritis reflects the pathogenic significance of these cytokines in disease. Stimulation of cells can reveal a latent deficiency in the synthesis of cytokines, which is not evident when determining its concentration in serum or supernatants of spontaneous whole-blood cultures.